Efficacy and safety of bexarotene combined with photo(chemo)therapy for cutaneous T‐cell lymphoma. Issue 5 (18th March 2020) - Morita, Akimichi; Tateishi, Chiharu; Muramatsu, Shinnosuke; Kubo, Ryouji; Yonezawa, Eri; Kato, Hiroshi; Nishida, Emi; Tsuruta, Daisuke
Abstract: Cutaneous T‐cell lymphoma (CTCL) is a chronic condition with low malignancy. International treatment guidelines for CTCL are widely followed in Europe and the USA. Combination therapy with therapeutic agents for CTCL and phototherapy is effective on the basis of European data. The efficacy and safety of combination therapy for Japanese CTCL patients are not established. We investigated the efficacy and safety of combination therapy with photo(chemo)therapy and bexarotene in Japanese CTCL patients. Twenty‐five patients received daily oral bexarotene (300 mg/m 2 body surface), followed by bath‐psoralen plus ultraviolet (UV)‐A (PUVA) or narrowband UV‐B. Treatment results were evaluated using the modified Severity‐Weighted Assessment Tool (mSWAT) and the Physician Global Assessment of Clinical Condition (PGA) up to week 24. Safety was also assessed. Twenty‐four weeks after initiating treatment, the total response rate was 80.0% (mSWAT) and 84.0% (PGA). Response rates did not differ when stratified by disease stage. Number of days (mean ± standard deviation) for time to response, duration of response and time to progression determined by the mSWAT were 20.7 ± 9.62, 117.0 ± 43.0 and 163.6 ± 28.8, respectively. T‐helper 2 chemokine levels in patients at stage IIA or more decreased significantly at weeks 12 and 24. All patients experienced adverse events and adverse drug reactions. Serious adverse drug reactions included sepsis, anemia and congestive cardiac insufficiency ( n  = 1 each). Other adverse drug reactions were of mild to moderate severity. Combination therapy with bexarotene and PUVA was safe and effective in Japanese CTCL patients.